MOTIVASI DAN DAMPAK BERMAIN GAME HIGGS DOMINO ISLAND DI KAMPUNG BUATAN II KECAMATAN KOTO GASIB KABUPATEN SIAK - Suryadi "; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted in Buatan II Village, Koto Gasib District, Siak Regancy, Riau Province. The purpose of this research is to find out: 1) peaple's motivation to play the higgs domino island game. 2) the impact of playing the higgs domino island game in Buatan II Village, Koto Gasib District, Siak Regancy. To achieve this goal, descriptive quantitative research using the slovin formula was used, the number of respondents was 102 respondents. This study uses simple random sampling through data collection techniques of observation, questionnaires, and documentation. The results of the research on pepale's motivation to play the higgs domino island game can be seen that there is a desire, and this desire arises because of good network access. There is hope and that hope is to gain victory. There is a need, and that need is the need to feel proud when you win. The existence of goal and objectives, and goals and objectives as entertainment. There is an incentive, abd that incentive is to earn money. The results of the research on the impact of playing the higgs domino island game can be seen that the positive impact of playing the higgs domino island game is that it can fill spare time. When resting after doing their respective activities, it turns out that the free time can be filled by playing the game higgs domino island. The negative impact of playing the higgs domino island game is that it makes you not remember the time. Playing until late at night making it difficult to get up early to do usual activities such as work, school Keyword: Motivation, Impact, Higgs Domino Island